1999
DOI: 10.1063/1.369968
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoimpedance effect in CoFeNi plated wire with ac field annealing destabilized domain structure

Abstract: Articles you may be interested inVery large magnetoimpedance effect in FeCoNi ferromagnetic tubes with high order magnetic anisotropy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 8 publications
(8 reference statements)
2
14
0
Order By: Relevance
“…The GMI effect can be defined as the change of impedance of a soft magnetic element carrying a high frequency current, as a function of the external dc magnetic field [1][2][3][4]. Investigations of the GMI effect have been quickly extended to ribbons and films [5][6][7][8][9][10][11][12][13][14][15]. Recently, the GMI effect has been observed in electroplated composite wires consisting of a highly conductive inner core and a magnetically soft outer shell, which plays an important role in determining the magnitude of the GMI effect.…”
Section: Introductionmentioning
confidence: 98%
“…The GMI effect can be defined as the change of impedance of a soft magnetic element carrying a high frequency current, as a function of the external dc magnetic field [1][2][3][4]. Investigations of the GMI effect have been quickly extended to ribbons and films [5][6][7][8][9][10][11][12][13][14][15]. Recently, the GMI effect has been observed in electroplated composite wires consisting of a highly conductive inner core and a magnetically soft outer shell, which plays an important role in determining the magnitude of the GMI effect.…”
Section: Introductionmentioning
confidence: 98%
“…It has also been reported that Cu wire plated with a 1-4 m thick NiFe magnetic layer shows large GMI effect. The magnitude of the GMI effect varies between 40% and 600% depending on the Cu wire diameter, electrodeposition parameters such as the pH of the solution, current density, plating time and composition of the solution [10,12,[13][14][15][16][17]. Therefore in this study, the effect of the NiFe film thickness plated on a Cu wire was investigated for the first time.…”
Section: Introductionmentioning
confidence: 98%
“…announced the appearance of the GMI effect in high permeability in NiFeMo permalloy wires [49]. Kurlyandskaya et al [50] have found an important GMI ratio in C06Ni2oFe64 thin films deposited on Cu-Be wire after a heat treatment in AC and DC fields.…”
Section: New Magnetic Materials Presenting Gmi Effectmentioning
confidence: 98%